Boxed In or Out? Balikbayan Boxes as Metaphors for Filipino American (Dis)Location - Alburo, Jade (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2005)
Balikbayan (from the Tagalog words balik, to return, and bayan, town or nation) boxes, which mostly contain pasalubong, or gifts, for relatives and friends, are staples in the transnational existence of many Filipinos and have come to represent the balikbayans, or the returning persons, themselves. Utilizing the rites of passage concept and the dialectic of gift-giving, reciprocity and reproduction, this article looks at balikbayan boxes as metaphors for the dislocation experienced and felt by many first-generation Filipino Americans. It presents the preparation of the boxes as an allegory for the bonds that bind Filipino Americans to those who remain in the Philippines. In reading these boxes as a location of balikbayan identity, it emphasizes the liminal status of first generation Filipino Americans both in their native and adopted countries.